PENDAMPINGAN PEMBELAJARAN TAJWID DENGAAN METODE NADA KETUKAN DI TPQ NURUSSALAM DESA KWASEN KECAMATAN BODEH - Irkham Nur Salim; Bahtiar Effendi (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2022)
This journal discusses a Tajwid learning method in TPQ Nurussalam Kwasen Village, Bodeh District, Pemalang Regency under the care of Ust.Saifullah where in the learning process a good and narratory method is needed so that it can make students easier and more enthusiastic in learning. In the discussion of the learning process method that we examined in this journal, it is more suggestive and refers to the learning method of Tajwid Science, so that the Beat Tone method is used to be accompanied by the appropriate speech tone and in rhythm with the short length of the Tajwid reading that is being studied. The learning results showed that the students of TPQ Nurussalam were able and faster in capturing the lessons delivered by the teacher.